Development Possibilities of the Port of Rijeka at the Beginning of the New Millennium - Dadić, Ivan; Kesić, Blanka; Hlača, Bojan (Promet - Traffic&Transportation, 2012)
The port of Rijeka, as part of the future system of the NorthAdriatic ports (Koper, Trieste, Rijeka) plays a significant role infreight transportation towards the Central European region. Bycons/meting the Danube - Sava Canal from Vukovar toSamac, by canalising the river Sava from Samac to Sisak, andby good railway and road connections that will be realised inthe first two to three decades of the third millennium the port ofRijeka will receive the key role in the development of the NorthAdriatic ports. High-quality railway and road connections betweenthe port of Rijeka and /stria, Koper and Trieste, will providemajor possibilities of rationalising the transportation processfrom the port of Rijeka towards the Danube region and theCentral European countries.